RANCANG BANGUN SISTEM INFORMASI BARANG KELUAR BERBASIS WEB PADA LINTAS MEDIA CIBINONG - BOGOR - Dudi Hariyadi; Hernando Luthfy Julianto (POLITEKNIK LP3I JAKARTA, 2023)
The problem of this study is based on the results of observations and observations made by the author at PT Jala Lintas Media, particularly in the process of managing goods in the warehouse. Based on these observations, it is known that the current system is still largely manual, especially in the process of issuing goods. This condition causes various problems, such as errors in the input and output of goods data, queues when picking up goods, and potential losses for the company due to errors in recording the quantity and type of goods issued. The manual system used is also considered ineffective in supporting the company's operational needs, which demand speed and accuracy of information. Thus, the information produced can be used as a basis for decision making. With the implementation of this information system, it is hoped that recording errors can be minimized, queues in goods collection can be reduced, and the effectiveness and efficiency of operational performance at PT Jala Lintas Media can be improved